Analysis of Renewable Energy Demands using AI - Karthick, Ramanathan; Mohsina, Mirza (INTI International University, 2023)
Sustainable energy includes all kinds of renewable energy which is obtained through the natural resources of our earth that are infinite or non-exhaustible, which includes mainly wind energy and solar energy. The future energy will be renewable energy which will be replacement for the traditional form of the energy which mainly depends on the fossil fuels which are detrimental to the environment. This paper mainly addresses the analysis of sustainable energy requirement for the future using artificial intelligence. Various types of renewable energy such as hydroelectric, wind and solar are taken into consideration for different seasons. Machine learning-based techniques will be used to preprocess the data and evaluate it for associations and trends. The total data is divided into two sets training and testing in the ratio of 80:20. The analysis of AI is done using python programming language. Finally, various types of machine learning techniques are compared for getting optimal results and tested also for accuracy. This paper can help analyze the renewable energy demands of future using machine learning and deep learning to deliver insightful information.